Anterolateral Corrective Lumbar Corpectomy and Interbody Fusion by Using Extended Screw Fixation without Posterior Instrumentation for Posttraumatic Kyphosis. (18th July 2013) - Yamazaki, Atsuro; Orita, Sumihisa; Sainoh, Takeshi; Yamauchi, Kazuyo; Suzuki, Miyako; Sakuma, Yoshihiro; Kubota, Go; Oikawa, Yasuhiro; Inage, Kazuhide; Nakata, Yukio; Inoue, Gen; Aoki, Yasuchika; et al.
Abstract : A 26-year-old paraplegic schizophrenic Japanese woman suffered from severe kyphosis and back pain derived from lumbar burst fractures caused by jumping. She had already undergone resection of the L1 and L2 spinous processes for sharp angular kyphosis, but she still had severe kyphosis and back pain at the L1 and L2. Radiographical examination revealed fused anterior columns at L1 and L2 with severe local kyphosis and a significantly decreased percutaneous distance in the back. The patient underwent anterior instrumented bony resection including an L2 vertebral osteotomy: bilateral L2-L3 facetectomy and partial posterior osteotomy of the L2 vertebrae via a posterior approach followed by an anterior corpectomy of the L2 vertebrae and insertion of a cylindrical cage. No posterior instrumentation was used owing to the presence of atrophied paraspinal soft tissues. Lumbar interbody fusion was performed with vertebral body screws extending from T12 to L4 and corresponding anterior distension and posterior compression. The procedure corrected the kyphosis by 15° and enhanced local stability. Postsurgical visual analogue scale improved from 9.0 to 2.0 and Oswestry Disability Index from 40 to 17.8, respectively. In conclusion, we have demonstrated that anterolateral interbody fusion using extended fixation can compensate for posterior corrective surgery.